METHOD OF HIGH-FREQUENCY OSCILLATION OF CHEST IN TREATMENT OF CHILDREN WITH RESPIRATORY PATHOLOGY - B.N. Babakhanova; I.K. Asherova ("Paediatrician" Publishers LLC, 2010)
Authors present an experience of high-frequency oscillation of chest via apparatus ?The Vest Airway Clearance System? in 194 patients from children's pulmonological hospital. The method was effective in complex treatment of acute and chronic bronchopulmonary pathology. Parameters of oscillations depending on age and type of respiratory pathology are proposed, its effectiveness according to the peak expiratory rate, excursion of chest, pulmonary radiograph are described. Authors give a description of possible unfavorable effects.Key words: children, clearance of airways, high-frequency oscillation of chest.(Voprosy sovremennoi pediatrii - Current Pediatrics. - 2010;9(3):117-120)